Extreme maldistribution of high field strength elements along subduction zones revealed by baddeleyite aggregates in serpentinite - Hikaru Sawada; Ryosuke Oyanagi; Sota Niki; Takafumi Hirata; Kazuki Yoshida; Mitsuhiro Nagata; Atsushi Okamoto (Scientific Reports)
Abstract Serpentinization along subducting plates induces mechanical mixing of diverse rocks and interaction with compositionally distinct fluids, which is often accompanied by the formation of rare mineral species. In this study, newly discovered baddeleyites in the Higuchi serpentinite body (HSB), Japan, are described. The HSB occurs as a 15 × 8 m outcrop surrounded by high-P/T metapelite, and baddeleyite was collected from only one serpentinite block. The baddeleyite appear as aggregates exhibiting angular or subrounded shapes with sizes of up to 2 mm in length. The aggregates are composed of acicular baddeleyite surrounded by porous zircon rims. Both the baddeleyite and the zircon yielded U–Pb ages of ca. 96 Ma, corresponding to the peak metamorphic age of the region. Within the aggregates, Th-enriched areas with sizes of less than 20 μm were observed. The baddeleyite aggregates show enrichment of light rare earth elements with positive Eu anomalies. Based on thermodynamic stability relationships, the baddeleyite aggregates are inferred to have originated as zircon megacrysts, which were mechanically incorporated into the ultramafic rock and subsequently metamorphosed during serpentinization. Subsequent metasomatism associated with carbonation and pervasive silicification led to the formation of the zircon rim and trace-elemental maldistribution. This study demonstrates significant high field strength elements (HFSE) heterogeneity on scales ranging from millimeters to micrometers within serpentinite along subduction zones.